2018
DOI: 10.2147/opth.s172846
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pupil dilation on predicted postoperative refraction and recommended IOL to obtain target postoperative refraction calculated by using third- and fourth-generation calculation formulas

Abstract: PurposeTo evaluate the influence of pupil dilation on predicted postoperative refraction (PPR) and recommended intraocular lens (IOL) power to obtain target postoperative refraction calculated by using the third- and fourth-generation IOL power calculation formulas with a new optical biometer.MethodsThis retrospective study included 162 eyes with cataract that underwent uneventful phacoemulsification with IOL implantation. PPR, recommended IOL power, anterior chamber depth (ACD), and lens thickness (LT) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
(21 reference statements)
5
22
0
1
Order By: Relevance
“…In our study, while ACD significantly increased after dilation, LT significantly decreased, which are both consistent with previous research [16]. WTW did not significantly change.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, while ACD significantly increased after dilation, LT significantly decreased, which are both consistent with previous research [16]. WTW did not significantly change.…”
Section: Discussionsupporting
confidence: 93%
“…Effective lens position is estimated based on ACD and AL in Haigis [2], and Barrett Universal II uses AL, corneal curvature radius, ACD, LT, and WTW [3]. Several studies have investigated the influence of pupil dilation on these biometric measurements [8,[10][11][12][13][14][15][16]. In a clinical setting, pupil dilation is a vital process of preoperative examination.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in good accordance with those previously reported between the OA-2000 and Lenstar 16 and between the Lenstar and IOLMaster 700 17 . Although LT was not used as a variable in the calculation of IOL power previously, the fourth-generation formula such as Olsen has taken this into account 18 . Therefore, the impact of LT difference on the refractive prediction error of pseudophakic eye may not be negligible in the new-generation formulas for IOL power calculation, and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Universal II changed most frequently among the formulas, although it was not statistically significant between Barrett Universal II and Haigis. Although some studies demonstrated that the recommended IOL power in Haigis was significantly affected by pupil dilation but not in SRK/T 10),12), 16) , our research was the first to show that Barrett Universal II may be even more sensitive to pupil dilation than Haigis, considering PPR and recommended IOL power. Haigis and SRK/T.…”
Section: Resultsmentioning
confidence: 55%
“…In our research, while ACD significantly increased after dilation, LT significantly decreased, which are consistent with other studies. 16) WTW did not significantly change. When it comes to the influence of pupil dilation on PPR and recommended IOL power, the outcomes of past research vary from formula to formula and from research to research.…”
Section: Resultsmentioning
confidence: 77%